PОSITIONAL GOOD: GENERAL CHARACTERISTICS AND MAIN FEATURES - Мирясов, Ю. О. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2012)
The article examines the concept of positional goods. By comparing the properties of private and public goods are marked features characteristic of positional goods, justified the possibility of using the properties of positional goods in the study of the concept of economic power.